THE VISIONS RELATED TO DOMESTIC ONIMALS (ON THE EXAMPLE OF SHEEP) IN THE VIEWPOINT OF FERGHONA VALLEY POPULATION (Scientific journal of the Fergana State University, 2023)
In this article analyzed viewpoint of people related to domestic animals, special with sheep on base field work materials. Disclosed place of sheep in life of human, values and forms of belief related with sheep among people.